Educação infantil: a afetividade no processo educativo na relação de cuidar, educar e socializar - LOBATO, Rosa Maria Carvalho (2019)
In the present work, entitled Infantile Education: the affectivity in the educational process in the relationship of caring, educating and socializing, a bibliographical study and a field research with the focus on the affection issues were sought, having as study element the affectivity in meaningful learning in Early Childhood Education, with children aged four (4) years, in a nursery in the municipality of Igarapé-Miri-PA. Therefore, the importance of the affective bond for learning is indisputable. Children who do not receive affection have serious commitments in several areas: cognitive, psychological and social. Educational actions need to establish an affective bond between school and family. Family issues are present in the life of the student, thus allowing a discussion between the school and family institution. The school and the family must establish a reciprocal relationship, where both need each other. In view of the above, this research presents an analysis about the issue of affections in the relationship of the child with teachers, with the family and with themselves, in the educational process, in the relationship of caring, educating and socializing. In this way, observation and data collection were carried out in the context where the children of Early Childhood Education develop their activities, and also, as the pedagogical practice of the ruling teachers of the class flows. Eventually, the results were analyzed and it was observed that the children are mostly very affective, feel cared for and loved by their parents. However, there was a need to work harder in the context of schooling. In view of this, the work aims to show the importance of affectivity in the educational process in the relationship of caring, educating and socializing, in the school environment within the framework of pedagogical practices in Early Childhood Education. Therefore, the theoretical background focuses on authors who have contributed a lot to the issue of affect as an element of the process of educating.